Pendidikan Berkelanjutan Melalui E-Learning bagi Perawat Suatu Program Inovasi - Rita Setianingrum; Rr. Tutik Sri Hariyati; Desnita Fitri (Journal of Telenursing (JOTING), 2021)
This study aims to analyze and develop learning methods to improve nurses' competence in continuing education through e-learning in inpatient rooms. The method used is a pilot project starting from data collection, problem analysis, determination of problem priorities, preparation of a plan of action, implementation and evaluation. The results showed that after e-learning learning, it was found that there was an increase in the knowledge of nurses in the surgical inpatient room with an average increase of 29.59% from pretest to posttest. 55% of patients' satisfaction with the quality of nursing care was satisfied, while 45% felt dissatisfied. The nurses' satisfaction who stated that the nurses were pleased with the nursing profession was 96%, while 4% of the total respondents were not satisfied with the 28 nurses. There were 12 nurses (agreed) and 16 nurses (strongly approved) from 28 respondents who stated that continuous training through e-learning could increase knowledge. In conclusion, the continuing education learning method through e-learning can improve nurses' competence in surgical inpatient rooms. Keywords: CPD, E-Learning, Satisfaction, Nurse